Cambodia : Technical Assistance Report-Government Finance Statistics Mission (April 26-July 15, 2021). (IMF Staff Country Reports; Country Report ;, 2022)
A follow-up technical assistance (TA) mission to the Ministry of Economy and Finance (MEF) was conducted remotely during 12 days over the period of April 26-July 15, 20211. This activity was part of Cambodia's participation in the Japan-funded Government Finance Statistics (GFS) and Public Sector Debt Statistics (PSDS) Project for selected Asian countries (JSA3)2. The mission liaised with Mr. Alexandros Mourmouras, Director of the Capacity Development Office in Thailand (CDOT), Mr. Rifaat Basanti, the IMF Regional JSA3 GFS/PSDS Project Manager, Ms. Delphine Anne Moretti, the IMF Regional Public Financial Management (PFM) Advisor for Southeast Asia, and Mr. Sean Craig, Macroeconomic Advisor - all in the CDOT, and Mr. Yasuhisa Ojima, the IMF's Resident Representative for Cambodia. The mission would like to thank the authorities for their excellent collaboration and support.